Seed coats of pulses as a food ingredient: Characterization, processing, and applications - Zhong, L.; Fang, Zhongxiang; Wahlqvist, M.; Wu, G.; Hodgson, J.; Johnson, Stuart (Pergamon Press, 2018)
Background: In recognition of their multiple benefits on environment, food security, and human health, pulses are attracting worldwide attention. The seed coat is a major by-product of pulse processing, and its only markets are as low value ruminant feed and very limited use in high fibre foods. Recently, accumulating studies have suggested that this underutilised by-product has greater potential as a novel natural “nutritious dietary fibre” which can be used as a functional food ingredient. Scope and approach: This review discusses biochemical and physicochemical functionalities of seed coats of six globally important pulses: chickpea, field pea, faba/broad bean, lentil and mung bean with a special emphasis on the emerging food pulse lupin. Food process modification and recent human food applications of the seed coats are summarized. Bio-availability of the seed coat compounds, and phomopsins contaminated lupin seed coats as a typical example of safety issue are discussed. Key findings and conclusions: High levels of dietary fibre, minerals and potential health-promoting phytochemicals in the seed coats indicate their great potential to be used as a natural “nutritious dietary fibre”. However, further in-depth studies are required to improve their desirable nutritional, physiological and techno-functional properties whilst minimizing any undesirable ones.